Penilaian keberhasilan pemberian Dental Health Education (DHE) menggunakan media video-modeling pada individu Gangguan Spektrum Autisme (GSA) pada masa pandemi COVID-19Dental Health Education delivering using Video-Modeling in Children with Autism Spectrum Disorder during Pandemic COVID-19 - Fa``Iqoh Zulfal Majidah; Risti Saptarini Primarti; Inne Suherna Sasmita (Padjadjaran Journal of Dental Researchers and Students, 2022)
ABSTRAKPendahuluan: Tantangan tenaga kesehatan dalam memberikan Dental Health Education (DHE) pada anak dan individu berkebutuhan khusus, salah satunya adalah penderita Gangguan Spektrum Autisme (GSA) yang memiliki gejala atau tanda berupa masalah perilaku, kesulitan dalam berkomunikasi, dan keterbelakangan kognitif. Individu GSA memiliki berbagai masalah medis yang menyertai (komorbiditas) termasuk masalah kesehatan di mulut.  Kondisi rongga mulut Individu GSA oral seperti oral hygiene yang buruk, karies, dan penyakit periodontal.  Tujuan penelitian adalah menilai keberhasilan pemberian Dental Health Education (DHE) menggunakan media Video-modeling (VM). Metode: Jenis penelitian deskriptif dengan teknik cross sectional. Pengambilan sampel secara total sampling dengan jumlah responden sebanyak 13 Individu GSA di Lembaga Pendidikan Autisma Prananda Kota Bandung. Kriteria penilaian keberhasilan pemberian DHE (video animasi cara menyikat gigi) menggunakan Object Retrieval Through Observational Learning Rating Criteria dengan skor 0 :  subyek gagal mengikuti instruksi yang diberikan; skor 1 : subyek  hamper tidak dapat mengikuti instruksi  yang diberikan; skor 2: subyek hampir dapat mengikuti instruksi, walaupun tidak berurutan seperti instruksi; Skor 3 : responden mengikuti seluruh instruksi yang diberikan dengan urutan yang benar. Hasil: Sebanyak 12 responden mendapat skor 2 dan 1 responden mendapat skor 1. Simpulan: Keberhasilan pemberian DHE dengan video modelling. pada masa pandemi COVID-19 pada Individu GSA adalah dapat mengikuti instruksi cara menyikat gigi.Kata kunci: dental health education; anak gangguan spektrum autisme; video-modeling ABSTRACTIntroduction The challenges of health workers in providing Dental Health Education (DHE) to children and individuals with special needs, one of which is children with autism spectrum disorders (ASD) who have symptoms or signs in the form of behavioral problems, difficulty in communicating, and cognitive retardation. Children with ASD have various accompanying medical problems (comorbidities) including oral health problems. Oral conditions in children with ASD include poor oral hygiene, caries, and periodontal disease. The purpose of the study was to analyzed  Dental Health Education (DHE) delivering using Video-modeling (VM) media. Methods: This research was a descriptive with cross sectional technique. Sampling with the number of respondents as many as 13 GSA children at the Pranada Autism Educational Institution, Bandung City. The criteria for assessing the success of giving DHE (animated video on how to brush teeth) using the Object Retrieval Through Observational Learning Rating Criteria with a score of 0: the subject failed to follow the instructions given; score 1: the subject can barely follow the instructions given; score 2: the subject can almost follow the instructions, although not sequentially like the instructions; Score 3: respondents follow all instructions given in the correct order. Results: A total of 12 respondents got a score of 2 and 1 respondent got a score of 1. Conclusion: Children with ASD are able to follow instructions on how to brush their teeth after being given DHE with video modeling. during the COVID-19 pandemic at the Prananda Autism Education Institute, Bandung City.Keywords: dental health education; autism spectrum disorder; video-modeling